Botanical Exploration in Baratang and Little Andaman Islands - Thothathri, K. (Indian Forester, 1975)
A botanical exploration was conducted in Baratang and Little Andaman Islands of the Andamans in 1964. The present paper deals with the vegetation and floristic studies of the these Islands. A systematic enumeration of the plants, collected is given.